PENGEMBANGAN MEDIA BIG BOOK BERBASIS WEB UPAYA PENINGKATAN KEMAMPUAN MEMBACA SISWA KELAS II SDN WONOSARI BONANG DEMAK - Fayrianto, Naufal; Panca Dewi Purwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research addresses the difficulties students face in understanding information from imaginative narrative texts. The study aims to describe the validation results and the effectiveness testing of web-based Big Book media. The research method used is R&D (Research and Development) with the Borg and Gall design. The subjects of the study were material experts and media experts. The subjects of the trial were 26 students and teachers. Data collection techniques in this study included observation, interviews, documentation, questionnaires, and tests. The results of this study are as follows: the results of validation from media experts obtained an average value of 88.57% with very feasible criteria. The results of validation from material experts obtained an average value of 81.66% with very feasible criteria. The effectiveness test in a small-scale trial with 6 Grade II students at SDN Wonosari Bonang Demak showed an average score of 85, categorized as good. Meanwhile, the large-scale trial involving 24 students in the same grade yielded an average score of 92.5, categorized as very good. It can be concluded that the web-based Big Book media is suitable and effective in enhancing reading comprehension skills among Grade II elementary school students.